Diagnosis and disease severity assessment of epidermolysis bullosa acquisita by ELISA for anti‐type VII collagen autoantibodies: an Italian multicentre study. (21st November 2012) - Marzano, A.V.; Cozzani, E.; Fanoni, D.; De Pità, O.; Vassallo, C.; Berti, E.; Parodi, A.; Crosti, C.; Cugno, M.
Summary: Background  Epidermolysis bullosa acquisita (EBA) is a rare autoimmune mucocutaneous bullous disease caused by autoantibodies against type VII collagen, a component of anchoring fibrils that stabilizes dermoepidermal adherence. Type VII collagen is composed of a collagenous domain linked by the noncollagenous (NC)1 and NC2 domains. Objectives  To assess the repeatability, sensitivity and specificity of a recently developed enzyme‐linked immunosorbent assay (ELISA) for detection of anti‐type VII collagen autoantibodies, and to ascertain whether they may be a marker of disease activity in EBA. Methods  Using this ELISA, which was able to recognize autoantibodies against the NC1 and NC2 epitopes of type VII collagen, we tested 14 EBA sera, 30 healthy control sera and 113 disease control sera. Results  In the EBA sera group, 12 out of the 14 samples were positive in ELISA, with autoantibody titres varying from 7·2 to 127·9 U mL −1 (cutoff value < 6), the sensitivity of the method being 86%. Among the controls, only two bullous pemphigoid sera tested positive, the specificity being 98·6%. A good correlation was found between EBA disease severity, expressed as autoimmune bullous skin disorder intensity score, and the serum levels of anti‐collagen VII autoantibodies, measured by ELISA ( n  = 14; r  = 0·965; P  = 0·0001). The intra‐ and interassay coefficients of variation of the ELISA method ranged from 6·3% to 18·3%. Conclusions  This NC1 + NC2 ELISA can be a practical assay for the diagnosis of EBA. The correlation between autoantibody titres and disease severity suggests its usefulness as a marker of disease activity in EBA However, this should be confirmed by studies on larger series of patients.